A fin design employing an inverse approach using simplex search method - Das, Ranjan. (2013)
This paper is aimed at estimating unknown parameters in a rectangular fin satisfying a predefined temperature. The differential transformation along with simplex method is used. The study has been done for different initial guess, random errors and measurement points. It is observed that, there is unique value of the convection-conduction parameter, but different conductivity and radiative parameters exist which will be useful in adjusting the parameters amongst various alternatives.